Religion and Social Capital of Citizenship: Bogor Islamic Community in a Globalizing World Development - Dundin Zaenuddin (UNHI PRESS, 2020)
Democratization is a globalized agenda of development that needs to be developed by the Indonesian society to achieve a just and prosperous country that is referred to as â€˜baldatun toyyibatun wa robbun ghofurâ€™ (Arabic, literally, â€œgood country under God forgivenessâ€). Within this framework, Islamic community (Islamic social organization) and other religious organizations are expected to behave kindly as an equal citizen that observe humanistic, pluralistic and tolerant religious social life. In this context, the situation of reciprocal trust, social solidarity, tolerance, equality, social networking even intra and extra-collective cooperation among socio-religious religious communities are expected to be more natural and sustainable. However, citizenship social capital still need to be develop through internalization and socialization. This research is based on the theories of Habitus of Bourdieu and Gellnerâ€™s Typology of Social Organization and Kymlickaâ€™s Multicultural Citizenship. This research also use other sociological theory namely the social capital theory of citizenship from Putnam, Coleman, Uphof, and religion-state relations theory from Boland, Menchik and Riaz Hassan. This research is qualitative with a multidisciplinary approaches of Sociology, Political Science, and History. The research findings show (1) the cosmopolitanism of the Bogor society is the factor that the various Islamic social organizations are accepted; (2) The social capital type of citizenship of Islamic social organizations is formed due to differences in religious and political orientation which are the resultant understanding of the texts and its religious culture; (3) Nahdhatul Ulama and Muhammadiyah with a moderate religious orientation (washitiyyah) have citizenship social capital that is persistent with democracy, while Hizbut Tahrir Indonesia and Front Pembela Islam with a fundamentalist religious style (ushuliyyah) have civic social capital that is resistant to Pancasila democracy.